IL-1β-induced modulation of gene expression profile in human dermal fibroblasts: the effects of Thai herbal Sahatsatara formula, piperine and gallic acid possessing antioxidant properties. Issue 1 (December 2017) - Thamsermsang, Onusa; Akarasereenont, Pravit; Laohapand, Tawee; Panich, Uraiwan
Abstract Background Pain is the main symptom of most musculoskeletal disorders and can be caused by inflammation in association with oxidative stress. Thai herbal Sahatsatara formula (STF), a polyherbal formula, has been traditionally used for relieving muscle pain and limb numbness. This study aimed to investigate biologically active compounds of STF and its pharmacological effects related to antioxidant and anti-inflammatory activities. Methods The identification of possibly active compounds of STF was performed by high performance liquid chromatography (HPLC). Moreover, this study also assessed the free radical scavenging activities of STF and its components using DPPH radical scavenging assay and their inhibitory effects on IL-1β-induced intracellular reactive oxygen species (ROS) formation in primary human dermal fibroblasts (NHDFs) using DCFDA-flow cytometry analysis. Modulation of human gene expression by STF and its active compounds was investigated by microarray analyzed through Gene Ontology (GO) classification and pathway enrichment analysis. Results HPLC analysis has revealed the presence of gallic acid (GA) and piperine (PP) as the major compounds in STF extracts. Our finding discovered that STF and its active compounds (GA and PP) yielded free radical scavenging activities and abilities to inhibit IL-1β-induced cellular ROS formation in NHDFs. Furthermore, microarray analysis demonstrated that a total of 84 genes (54 upregulated and 30 downregulated) were significantly affected by IL-1β involved in inflammatory cytokines, chemokines, transcription factors, cell adhesion molecules and other immunomodulators participating in NF-κB signaling. The significantly upregulated genes in IL-1β-treated in NHDFs participate in interleukin and cholecystokinin (CCRK) signaling pathways. The GO analysis of the target genes showed that all test compounds including indomethacin, STF and its active compounds, can downregulate the genes involved in NF-кB signaling pathway in IL-1β-treated NHDFs compared to the cells treated with IL-1β alone. Conclusions STF and its active compounds possessing antioxidant actions can modulate the effects of IL-1β-mediated alteration of gene expression profiles associated with inflammatory signaling in NHDFs.